2018
DOI: 10.1002/brb3.952
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral changes induced through adenosine A2A receptor ligands in a rat depression model induced by olfactory bulbectomy

Abstract: BackgroundMajor depressive disorders are characterized by their severity and long‐lasting symptoms, which make such disorders highly disabling illnesses. Unfortunately, 50% of major depressive patients experience relapses, perhaps partly because drug research has been performed only in animal models that screen for antidepressant drugs that appear to only ameliorate acute depression symptoms. The bilateral olfactory bulbectomy (OBX) animal model presents the advantage of mimicking the symptoms of chronic depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…Consistently, selective A2A antagonists have attracted attention for their possible role in the treatment of depression. Preclinical studies highlighted that A2A antagonists have antidepressant effects [39][40][41][42] and may potentiate responses to antidepressant treatment [43], whereas A1 antagonists do not [44]. The A2A selective antagonist istradefylline (KW6002), recently approved by the FDA as an add-on therapy for off episodes in adults with Parkinson's disease [45], may also be effective in treating depressive-like symptoms, with an effect that is independent from monoaminergic transmission in the brain [46].…”
Section: Adenosine and Depressionmentioning
confidence: 99%
“…Consistently, selective A2A antagonists have attracted attention for their possible role in the treatment of depression. Preclinical studies highlighted that A2A antagonists have antidepressant effects [39][40][41][42] and may potentiate responses to antidepressant treatment [43], whereas A1 antagonists do not [44]. The A2A selective antagonist istradefylline (KW6002), recently approved by the FDA as an add-on therapy for off episodes in adults with Parkinson's disease [45], may also be effective in treating depressive-like symptoms, with an effect that is independent from monoaminergic transmission in the brain [46].…”
Section: Adenosine and Depressionmentioning
confidence: 99%
“…Authors also evidenced that A2A receptor is a major regulator of GR function since its inhibition reduces GR hippocampal levels, and acts on GR nuclear translocation and GR-dependent transcriptional regulation ( Batalha et al, 2016 ). Interestingly, some studies showed an anti-depressive effect of A2A receptor antagonists in MDD models ( López-Cruz et al, 2018 ; Padilla et al, 2018 ). A2A receptor is an example among others.…”
Section: Gr a Potential Therapeutic Targetmentioning
confidence: 99%
“…Administration of ZM 241385, an inhibitor of A 2A receptor, decreases the immobility and isolation time in a rat depression model, indicating that activation of A 2A receptor contributes to depressive behaviour. 189 Consistently, rats overexpressing A 2A receptor demonstrate depressive phenotypes. 190 In contrast, stimulation of A 1 receptor exhibits antidepressant effects.…”
Section: Purinergic Neurotransmission In Neurodevelopment and The Pathogenesis Of Brain Diseasesmentioning
confidence: 93%